Energy alignment and recombination in perovskite solar cells: weighted influence on the open circuit voltage. Issue 4 (25th March 2019) - Gelmetti, Ilario; Montcada, Núria F.; Pérez-Rodríguez, Ana; Barrena, Esther; Ocal, Carmen; García-Benito, Inés; Molina-Ontoria, Agustín; Martín, Nazario; Vidal-Ferran, Anton; Palomares, Emilio
Abstract : In this work, we assess the possible reasons for the differences observed in open circuit voltage ( V OC ) in mixed cation perovskite solar cells when comparing four different hole transport materials (HTMs), namelyTAE-1, TAE-3, TAE-4 andspiro-OMeTAD . Abstract : In this work, we assess the possible reasons for the differences observed in open circuit voltage ( V OC ) in mixed cation perovskite solar cells when comparing four different hole transport materials (HTMs), namelyTAE-1, TAE-3, TAE-4 andspiro-OMeTAD . All these HTMs present close chemical and physical properties, however, once they are finally deposited onto the perovskite layer, the HTMs provide different performance characteristics. Additional to the evaluation of the HTM influence on recombination, we find that, upon deposition of the organic HTM on top of the perovskite, there is an important change in the energy level position, and the impact on the device V OC is discussed. We consider that this experimental observation could be general for other organic HTMs and would justify the difficulties in finding molecules and materials that could improve the efficiency of perovskite solar cells overcoming the solar-to-energy conversion efficiency of solar cells made usingspiro-OMeTAD as a hole selective contact.